Productivity, Technology and Innovation Capacity and Dissemination of Technology in Modern Commercial Agriculture in Peru: A Regional Exploratory Analysis - Tello, Mario (2016)
This paper, exploratory in nature, analyzes and estimates the relationships between the technological and innovation capacity (CTI), diffusion of good technological practices and labor productivity of productive units of the agricultural sector undertaken by family chiefs selling their production to (domestic and external markets) and of legal conditions of ‘natural persons’ of Peru. The main source of information is the National Agricultural Census of 2012. The three main results of the estimations point out that unit sizes, family chiefs’ human capital accumulation and the geographic distance between the location of the productive unit and the capital of the district of that location were key statistical factors that determined the producer technological and innovation capacity. This CTI together with the spillover effects coming from producers associations determined the diffusion and use of technological good practices. Finally, the stock of land per workers was the key determinant of labor productivity in all the regions of Peru.